Individual differences in the relationship between episodic detail generation and resting state functional connectivity vary with age. (10th February 2022) - Matijevic, Stephanie; Andrews-Hanna, Jessica R.; Wank, Aubrey A.; Ryan, Lee; Grilli, Matthew D.
Abstract: The ability to generate episodic details while recollecting autobiographical events is believed to depend on a collection of brain regions that form a posterior medial network (PMN). How age-related differences in episodic detail generation relate to the PMN, however, remains unclear. The present study sought to examine individual differences, and the role of age, in PMN resting state functional connectivity (rsFC) associations with episodic detail generation. Late middle-aged and older adults (N = 41, ages 52–81), and young adults (N = 21, ages 19–35) were asked to describe recent personal events, and these memory narratives were coded for episodic, semantic and 'miscellaneous' details. Independent components analysis and regions-of-interest analyses were used to assess rsFC within the PMN separately for anterior connections (hippocampal and medial prefrontal) and posterior connections (hippocampal, parahippocampal and parieto-occipital), as these connections purportedly serve different functional roles in episodic detail generation. Compared to younger adults, older adults produced memory narratives with lower episodic specificity (ratio of episodic:total details) and a greater amount of semantic detail. Among the older adults, episodic detail amounts and episodic specificity were reduced with increasing age. There were no significant age differences in PMN rsFC. Stronger anterior PMN rsFC was related to lower episodic detail in the older adult group, but not in the young. Among the older adults, increasing age brought on an association between increased anterior PMN rsFC and reduced episodic specificity. In contrast, increasing age brought on an association between increased posterior PMN rsFC and increased semantic detail. The present study provides evidence that functional connectivity within the PMN, particularly anterior PMN, tracks individual differences in the amount of episodic details retrieved by older adults. Furthermore, these brain-behavior relationships appear to be age-specific, indicating that some process within aging alters the nature of how anterior PMN rsFC and episodic detail relate to each other. Whether this process entails an age-related loss of integrity to the PMN, or an age-related shift toward semantic retrieval, remains to be determined. Highlights: Age differentially impacts episodic and semantic detail generation. MTL-neocortical resting state functional connectivity (rsFC) does not vary with age. Stronger MTL-neocortical rsFC relates to lower episodic detail generation among older adults. Associations between MTL-neocortical rsFC and episodic detail generation are age-dependent.